Resisting Colonial Discourse: Edward Said and Speaking Truth to Power - Sazzad , Rehnuma (EAST WEST JOURNAL OF HUMANITIES, 2010)
I am for dialogue between cultures and coexistence between people: everything I have written about and struggled for has pointed to that as the goal. But real principle and real justice have to be implemented before there can be true dialogue (Said, Quoted in Bove, 1).